A New Look at National-state Transformations in the South of the RSFSR: Book Review: Gunaev E. A. National Autonomies of the South of Russia in the Soviet Period: Territorial Structure and Management System (using the example of Kalmykia) / resp. ed. K. N. Maksimov. Elista: KalmSC RAS, 2022. 400 p. - 10.22162/2500-1523-2024-1-165-172 (Монголоведение)
The review was devoted to the monograph by E. A. Gunaev (Kalmyk Scientific Center of the Russian Academy of Sciences) “National Autonomies of the South of Russia in the Soviet period: Territorial Structure and Management System (on the example of Kalmykia)” (Elista: KalmSC RAS, 2022. 400 p.). The monograph was written on the basis of a wide range of sources and literature, including 30 files from 6 funds of 3 state archives, 425 publications of documents and research. E.A. Gunaev identified three stages in changing the administrative-territorial structure and management system in the national autonomies of the South of Russia: 1920–1943, 1944–1976, 1977–1991. Each stage is presented in a separate chapter of the monograph. The author proposed a historical and legal analysis of the problems under consideration with an emphasis on the study of regulatory aspects. Of significant interest is the study of the problem of legal succession between national autonomies, recreated after the rehabilitation of repressed peoples, and their national-state formations before forced eviction. E.A. Gunaev distinguishes between the categories of continuity, legal continuity and succession, and analyzes the possibilities of their use within the framework of the issue under consideration.